Asymbiotic germination and morphological studies of seeds of Atlantic Rainforest micro-orchids (Pleurothallidinae) - Koene, Franciele Marx (PLoS One, 2020)
The morphological and morphometric characters of seeds belonging to 11 species of the subtribe Pleurothallidinae using light and scanning electron microscopy were studied to understand the in vitro germination process. Qualitative data (color, shape, ornamentation) and quantitative ones were also evaluated in seeds and embryos (length, width, volume and air space percentage between the integument and the embryo). The viability of the seeds was evaluated by in vitro germination in woody plant medium (WPM), and by analysis of the developmental stages of protocorms until seedling formation (two to 24 weeks). Morphometric data showed variations within the genus Acianthera and between species of different genera. The best germination and protocorm formation responses occurred with Acianthera prolifera (92%) and Acianthera ochreata (86%), with the formation of seedlings after 12 and 16 weeks of sowing, respectively. The seeds and embryos of A. prolifera and A. ochreata were larger (length, width, and volume) with a structural polarity that may have facilitated their germination comparing to others studied species. Other characteristics of A. prolifera seeds that may have contributed to these results include the presence of a thin testa without ornamentation and a suspensor. The protocorms of Anathalis obovata, Dryadella liliputiana, and Octomeria gracillis developed slowly in the WPM, not reaching the seedling stage in 24 weeks of cultivation. This morphological and morphometric study contributes to the understanding of asymbiotic germination of some micro-orchid species.